STRATEGI PEMERINTAH KOTA PEKANBARU DALAM PENGEMBANGAN KEBUDAYAAN MELAYU TAHUN 2008-2013 - Putri, Triananda; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Constitution of Indonesia is guarenteed about cultural vision on Article 28 paragraph (3) , Article 32 paragraph (1) and paragraph (2). Cultural aspects must considered in the government's strategic policy development. Malay culture being identity of Pekanbaru city and want to be center of Malay culture. Achieving the vision set by well-directed strategy. Development of strategy should be considered to 7 element of universal culture. In 2009, population of Pekanbaru dominated by Minang ethnic in the range of 37.7 % , while the ethnic Malays in the range of 26.1 % .Malay cultural as open characteristic make the process of acculturation not inevitable. The seriousness of the government in planning and implementing of development strategy Malay culture is needed to maintain identity of the city . Implementing strategy of culture development influence by competency of human resources, affirmation of relevant institution, availability of facilities and infrastructure and financial. However, strategy implemanting couldn’t be success if civil society nothing partisipation for support this vision.Keyword : Strategy, development of culture, Malay